ВИЗНАЧЕННЯ ЕНЕРГЕТИЧНИХ ХАРАКТЕРИСТИК ІНФОРМАТИВНИХ СИГНАЛІВ ДЛЯ ЗАБЕЗПЕЧЕННЯ ЇХ СТІЙКОЇ ІДЕНТИФІКАЦІЇ В ЗАДАЧАХ ТЕЛЕМЕДИЦИНИ - КУЛИК, АНАТОЛІЙ ЯРОСЛАВОВИЧ; Коваль, Борис Федорович; РЕВІНА, ТЕТЯНА ГРИГОРІВНА; БОДНАР, МАРІЯ ВІКТОРІВНА (Vinnytsia National Technical University, 2018)
An analysis of the information transmission system was carried out under the condition of informative signal identification according to the Kotelnikov criterion. This allowed us to determine the signal-to-noise ratio at the input and output of the communication channel, as well as the probability of errors in the identification of an elementary signal for different transmission conditions.